2010
DOI: 10.2176/nmc.50.373
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Preoperative Evaluation of Patterns of Drainage of the Cavernous Sinus in Patients Treated Using the Anterior Transpetrosal Approach

Abstract: Extradural procedures in an anterior transpetrosal approach (ATPA) may interrupt the route of drainage from the superficial middle cerebral veins (SMCVs) and the cavernous sinus (CS) to the pterygoid venous plexus at the temporal skull base. Patterns of drainage of the SMCV and the CS and the results of surgery were examined in 12 patients with petroclival lesions treated using the ATPA between 2000 and 2008. The angiographic patterns of drainage of the SMCV were examined in 22 sides of the 12 patients. The SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…4A). 4,10 The middle meningeal artery is coagulated and cut. The GPN is dissected in the interdural layer to preserve the nerve.…”
Section: Basic Concept Of the Atpamentioning
confidence: 99%
See 1 more Smart Citation
“…4A). 4,10 The middle meningeal artery is coagulated and cut. The GPN is dissected in the interdural layer to preserve the nerve.…”
Section: Basic Concept Of the Atpamentioning
confidence: 99%
“…21 Hayashi et al reported a relationship between the venous pattern encountered in the ATPA and surgical results. 10 They concluded that venous drainage from the CS should In Type 2b, we should perform an epidural anterior petrosectomy with subdural visualization of the SBV (E). F-h: Comparison of Types 3a-c.…”
Section: 6729mentioning
confidence: 99%
“…Sphenoidal emissary veins (Vesalian or Meckel's veins) connect the cavernous sinus with the pterygoid or pharyngeal plexuses (Dwight et al 1913;Gray 1918;Hayashi et al 2010). These veins are not constant and are only found in approximately one in three cases (Dwight et al 1913).…”
Section: Sphenoidal Emissary Vein (Vesalius)mentioning
confidence: 99%
“…A sphenoidal emissary foramen is present in 20% of individuals, which is located at the root of the greater sphenoid wing medial to the foramen ovale. This foramen contains an emissary vein connecting the CS and pterygoid venous plexus, which may be a source for bleeding during lateral extradural dissection [32,35]. Extensive dissection of the ICA may result in injury and leaving tumor remnants attached to important blood vessels is often prudent.…”
Section: Complication Avoidancementioning
confidence: 99%